RELASI AGAMA DAN BUDAYA DALAM TRADISI NGURISANG MASYARAKAT ISLAM SASAK - AMINAH, SITI; SUHASTINI, NOVIA (Universitas Islam Negeri (UIN) Mataram, 2021)
Religion is a guide for human life regarding divinity, while culture is a habit, a procedure for human life created by humans themselves which originate from creation, taste and intention as a gift from God. In everyday life, religion and culture are often juxtaposed and even inseparable, especially in some of the ceremonies and rituals that are carried out by the Sasak Islamic Community. In the Ngurisang tradition, for example, we can see a strong relationship between religion and culture. The formulation of the problem in this study is First: What is the meaning of Ngurisang in terms of religion and culture? And Second: how is the relation between religion and culture in the tradition of Ngurisang in the Sasak Islamic Society?. The purpose of this study was to determine the meaning of Ngurisang in terms of religion and culture. As well as to find out the relationship between religion and culture in the Ngurisang tradition of the Sasak Islamic Society. This research uses descriptive qualitative method. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The theory used as an analytical knife is the theory of Viktor Turner's ritual symbols. The results showed that the Ngurisang tradition in the Sasak Islamic Society in terms of religion can be juxtaposed with the term aqiqah. Meanwhile, in the cultural context, you have to go through three ritual stages, namely silver fire, goat slaughter and Ngurisang. Then there is a very strong religious and buya relationship in each of the Ngurisang processions.